An Investigation of the Factors Leading to Underpricing in the Norwegian IPO Market. - Barfod, Jonathan Andreas (2009)
This paper examines the Norwegian market for Initial Public Offerings (IPOs) for the period 1998-2008, and conducts an analysis of what factors have led to an average underpricing of 3.66%. It is discovered that whilst the risk level of a firm is irrelevant to its initial return when going public, there is a strong relationship between the contract type that is utilized and the level of underpricing. Evidence of how setting the final IPO price early affects initial returns positively is also presented. Furthermore, two final models are developed that include different industry sectors, and explain the expected initial return for the time period. Finally, an additional analysis concludes that the market has witnessed greater activity and more IPOs, when the stock exchange has increased substantially along with the oil price.